Graph-based Framework for Road Network Performance and Flood Risk Assessment - ICASP14; He, Ke; De Risi, Raffaele; Pregnolato, Maria; Carhart, Neil; Neal, Jeffrey (My University, 2023)
The road network provides a connecting infrastructure that facilitates countless daily pursuits, supporting communication and economic activity. Flooding hazard often threaten the road network with physical damage and service interruption. Traffic disruptions are reflected in increased travel distance, increased travel time, and even inability to travel at all. This paper proposes a framework combining flooding scenarios and road network topological features to assess road network performance and risk. A graph-based model is introduced to assess the global network performance in terms of connectivity and accessibility. This model also allows to identify the critical components in the road network. The flood hazard is then presented in terms of flood depth and velocity for multiple return periods. Flood intensity maps are used to assess the vehicle risk of degraded driving performance on the entire network. The methodology is applied for the road network of Bristol, UK. Flood scenarios with 10-year and 200-year return periods are considered. The results presented herein may be used to support the development of mitigation strategies to improve the resilience of road networks.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED